Performance and emission opacity of canola and soybean biodiesel fuel in a diesel engine - Taib, Norhidayah Mat; Zainuddin, M.S.; Mansor, Mohd Radzi Abu; Ilham, Zul (Universiti Malaysia Pahang, 2018)
Biodiesel is a renewable fuel known to produce more environmentally friendly emissions compared to diesel fuel. However, at times it has been reported as exhibiting a much lower engine performance compared to standard diesel fuel. Biodiesel fuel has the potential to achieve similar performance as compared to diesel fuel when the optimum percentage of biodiesel blend is used. In this study, an experiment was conducted to determine the performance and opacity of emissions collected from soybean biodiesel and canola biodiesel fuel by using a YANMAR TF90 single cylinder direct injection diesel engine. The objective of this study is to determine the best percentage of diesel-soybean and diesel-canola fuel mixture that would result in the best performance of an engine. The experiment investigated the brake specific fuel consumption (BSFC), brake thermal efficiency (BTE), brake power (BP), and torque generated by the engine using different biodiesel fuel percentages at varying engine speeds. Additionally, the emission opacity was investigated to identify the most favourable fuel percentage for optimised biodiesel compared to the quality obtained from soybean and canola soybean biodiesel. The results from the experiment clearly show that the engine using biodiesel fuel has a slightly lower performance as compared to the engine that only used diesel fuel for all percentages used. However, at low speeds, a BTE of 40% canola biodiesel was higher compared to diesel and soybean biodiesel. The BSFC for all biodiesel fuel was found to be slightly higher than diesel, except for BC40, which was greater for BSFC compared to other blends used at much lower engine speeds. Engine emission opacity of biodiesel was recorded to be less than diesel fuel at all engine speeds, but slightly higher for BC5, BS5 and BS20 due to the insufficient air intake to the engine. Engine performance and emission opacity of all biodiesel fuels were found to be similar to diesel fuel. From the results relating to engine performance and emission, canola biodiesel was found to be an excellent biodiesel product to be used in a diesel engine since it had a higher BTE, lower BSFC and a lower opacity which was greater than those of soybean biodiesel blends. Therefore, biodiesel can be blended in a diesel engine at a higher percentage while maintaining engine performance and reducing engine emission.